Evaluation of axillary lymph node metastasis in relation to size and metastatic status of sentinel lymph node in carcinoma breast - Pandey, Vineet Kumar; Ghuliani, Deepak; Neogi, Sushanto; Khurana, Nita; Jindal, R. K. (International Surgery Journal, 2019)
Background: Sentinel lymph node (SLN) is the first node in the nodal basis of a tumor and the most likely site for earliest lymph node metastasis. Modified radical mastectomy with axillary lymph node dissection (ALND) has been the standard of care for carcinoma breast. The SLN is the only involved node in majority (40-70%) of the patients undergoing ALND for a positive SLN biopsy. ALND is associated with significant morbidities like seroma, infection, lymphedema and nerve injury. The purpose of this study was to evaluate the axillary node metastasis with respect to the size and tumoral load of positive SLN. Methods: Thirty patients of biopsy proven early breast carcinoma underwent SLN biopsy with methylene blue dye followed by modified radical mastectomy (MRM). After measuring the size of the SLN with Vernier caliper, SLN and MRM specimen were sent for histopathological examination. Status of non-sentinel ALNs was compared with the size and tumoral load of SLN. Results: Among 30 patients, 5 patients had positive SLN. Patients with positive SLNs were younger (mean 36 vs. 52 years), had larger diameter (10.8 vs. 7.4 mm, p<0.03) with higher number of non-sentinel ALN metastasis (35% vs. 4.86%). Macrometastasis in positive SLN was associated with higher risk of metastasis to non-sentinel ALNs. Conclusions: A SLN size of more than 7.5mm has higher risk of harboring metastasis. A SLN size higher than 10mm and macrometastasis is associated higher risk of metastasis to non-sentinel ALNs.